The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1603/0022-0493-93.6.1788
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Reversion of Azamethiphos-Resistance in a Field Population of the Housefly <I>Musca domestica</I> (Diptera: Muscidae), and the Underlying Biochemical Mechanisms

Abstract: The organophosphorus insecticide, azamethiphos, is widely used throughout the world to control the housefly, Musca domestica (L.). Since its commercial introduction to Denmark in 1983 for this purpose, we have monitored the toxicity of azamethiphos to housefly populations at livestock farms throughout the country and carried out regular field studies. The findings of our field studies, which have revealed a strong potential for resistance development, have been born out by regular surveys showing that resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…These counts increased dramatically to 150 and 198 vector species in 1980150 and 198 vector species in and 1990150 and 198 vector species in , respectively (WHO 1992. In addition, several studies, such as Elyassaki (1986), Kasai and Scott (2000), Kristensen et al (2000), and Kočišová et al (2002), reported that house flies have started developing resistance against synthetic pyrethroids, as well as various other insecticide groups recently. The same results were found in studies conducted in Turkey (Tezok et.…”
Section: Discussionmentioning
confidence: 99%
“…These counts increased dramatically to 150 and 198 vector species in 1980150 and 198 vector species in and 1990150 and 198 vector species in , respectively (WHO 1992. In addition, several studies, such as Elyassaki (1986), Kasai and Scott (2000), Kristensen et al (2000), and Kočišová et al (2002), reported that house flies have started developing resistance against synthetic pyrethroids, as well as various other insecticide groups recently. The same results were found in studies conducted in Turkey (Tezok et.…”
Section: Discussionmentioning
confidence: 99%
“…Such studies unveil the mechanisms and mode of inheritance of insecticide resistance, its stability and crossresistance to other insecticides which ultimately lead to a more probable estimation of resistance risks in insect pests, and management of this resistance. The genetic basis of insecticide resistance has been well documented in different insect pests around the world: For example, Cydia pomonella from France (Bouvier et al 2001), Helicoverpa armigera from Australia (Daly and Fisk 1992), Plutella xylostella form Malaysia (Sayyed and Wright 2001), Spodoptera litura from Pakistan (Ahmad et al 2007), Musca domestica from China (Shi et al 2011), the United States (Kaufman et al 2010) and Denmark (Kristensen et al 2000). However, there is a lack of information at Pakistan level.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in resistance levels may be due to the negative effects of resistance genes on fitness components without insecticide selection pressure. When insecticide exposure is not a constant factor, the susceptibility of resistant individuals may change in the absence of selection pressure under laboratory conditions (Abbas et al 2014b;Kristensen et al 2000;Roush 1993).…”
Section: Introductionmentioning
confidence: 99%